Project smoke : seven steps to smoked food nirvana, plus 100 irresistible recipes from classic (slam-dunk brisket) to adventurous (smoked bacon-bourbon apple crisp) - Raichlen, Steven (Workman Publishing, 2016)
"Describes Raichlen's seven steps to smoked food nirvana, including choose your smoker, source your fuel, [and] know when your food is done. There's an in-depth rundown on various smokers; the essential brines, rubs, marinades, and barbecue sauces; ... a complete exposition of woods; and ways to smoke--cold smoking, hot smoking, smoke-roasting and smoke-braising"--